Diffusion of moisture and oxygen in bitumens using electrochemical impedance spectroscopy. (1st May 2022) - Chen, Mingyuan; Geng, Jiuguang; Chen, Huaxin; Niu, Yanhui; Wang, Ronghua; Wu, Wanzhen; Zhao, Shungen; Zhong, Zhihua
Highlights: EIS was used to study the diffusion of water vapor and oxygen in bitumen. With the growth of duration, temperature and humidity, the impedance arc of bitumen gradually decreased in the Nyquist plot. Temperature and humidity had a great influence on the diffusion coefficient of moisture and oxygen in bitumen. Abstract: The moisture and oxygen in the air continue to diffuse to the bituminous pavement, causing moisture damage and water aging. In this paper, the electrochemical impedance spectroscopy (EIS) test was carried out through changing duration, temperature and humidity to determine the average diffusion coefficient of different bitumens. The results show that the increase of duration, temperature and humidity would cause the impedance arc of bitumen to shrink and the impedance modulus to decrease. The capacitance parameters obtained by fitting also increased significantly with duration, because the dielectric constant of bitumen and the polar groups caused by water aging increased with the continuous penetration of water vapor and oxygen possibly. Further, based on the Continuous model, temperature and humidity had a significant effect on the coupled diffusion coefficient of water vapor and oxygen in the bitumens.